The Bioactive Compound and Mechanism of Action of Sea Cucumber (Holothuridae) as Anticancer: A Review - Diah Anggraini Wulandari; Gita Syahputra; Masteria Yunovilsa Putra (Chemistry Department, The University of Brawijaya, 2020)
The extreme development and resistance towards cancer drugs, and also the high toxicity, drug resistense and side effects of some cancer chemotherapy drug triggers us to develop new drugs as one of the alternative substitutes or combinations of cancer drugs, one of the resources come frome marine biodiversity especially sea cucumber. The bioactive compound from sea cucumber can inhibit cencer cell growth with the various mechanism. This study aims to analyze chemichal composition, bioactive compound from sea cucumber to inhibit cancer cell line and to analyze mechanism of action of sea cucumber as anticancer wih the most recent research studies. The result shows sea cucumber contained protein 44-82%, amino acid, fatty acid, collagen, peptide, micro essential. Each sea cucumber species produce the different secondary metabolites that can use as anticancer. Sea cucumbers contain triterpene glycosides, saponins, Holothurin A, sti-choposides, frondoside, cucumariosides, Dsechinoside, fucoidan, triterpenoid aglycones (philinopgeni), non-glycosaminoglycan, sulfated glycans, sulfated polysacchidides,non-glycosaminosides) that can inhibit cancer cell line. That bioactive compound had a various mechanism such as apoptosis in cell line and mitocondria, Antioksidan mechanism,and membranolitic.